The Round Allograph of in Late Middle English - Thaisen, Jacob (Studia Anglica Posnaniensia, 2018)
This paper discusses glyphs of the 2-shaped or “round” allograph of the grapheme <r> with a tag protruding from the lower part of the stem, asking whether their distribution in a corpus of some 600 late Middle English texts can be meaningfully related to these texts’ localisation in A Linguistic Atlas of Late Mediaeval English. It discusses what localisation expresses, and uses regression modelling to show that there is no co-variation between the texts’ paleography and their orthography, although there is a measure of correlation between them. The evidence in favour is that the quantitative analysis identifies localisation in northings as a predictor of the occurrence of the tagged form of the allograph, which occurs at a higher frequency in texts localised below the Midlands line at c. 300 northings. The evidence against is the form’s scattered distribution according to the localisation variable where co-variation would imply a more clear-cut concentration of points, and also the moderate success at explaining the form’s distribution by means of variables known to explain orthographic variation.